Molecular Docking Recent Advances - Salih Istifli, Erman (Biomedical Engineering, 2023)
Molecular docking is a widely used bioinformatics method in biology, medicine, and biochemistry. This method, which can model interactions between different receptors and their various ligands at the molecular level, can represent intermolecular interactions at an unprecedented resolution that may not be achieved by classical experimental approaches. This book describes different aspects of this method that can reveal the intermolecular biochemical and biophysical interactions and the affinities of partner molecules to each other. It is designed for academics, students, and professionals interested in this technique.